KAWIN KONTRAK: LATAR BELAKANG,KEABSAHAN HUKUM DAN DAMPAKNYA(STUDI KASUS DI KABUPATEN JEPARA) (Forum Ilmu Sosial, 2013)
Marriage of contract is one means for foreigners doing business in Jepara furniture. Contract marriages are not merely a biological needs or sex of the foreign men, but also as a way for them to continue and develop its business in Jepara. The practice of contract marriages in the district of Jepara raises its own problems, especially with regard to the legal validity and impact. That problem revealed after research to him primarily through qualitative research approach. From the data analysis and discussion of sufficient depth to the results, it can be concluded that the economic needs of the dominant factor that causes women want to undergo marriage of contract Jepara. Contract marriage they lived did not have legal validity, both in terms of the National Marriage Law and the views of the Compilation of Islamic Law. Legal protection for the wife and kids there because their marriage is  not valid. For those who contract marriage with siri way, during the ongoing marriage law has not yet felt the impact. After the marriage broke up, the impact of the law was that the ex-wife can't claim property gono-gini and legacy. After married to foreign men, women Jepara changing cultural value system of Javanese culture to European culture, for example, from less efficient to be efficient, from the communal be individualized, and so on.